ANALYSIS OF THE INFLUENCE OF ENTREPRENEURSHIP SELF-EFFICACY AND ENTREPRENEURIAL INNOVATION BEHAVIOR ON SMES BUSINESS PERFORMANCE IN TANGERANG MEDIATED BY LEADERSHIP AND ENTREPRENEURIAL MOTIVATION - Michael Aaron Tianda; Oscar Jayanagara (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2025)
One of the pillars of the economy in Indonesia that plays a role in economic growth is MSMEs. The development of MSMEs in Indonesia is influenced by internal entrepreneurial factors, namely entrepreneurial innovative behavior, entrepreneurial leadership, entrepreneurial self-efficacy, and entrepreneurial motivation, by taking the object of research as MSME actors in Greater Tangerang. This study aims to analyze the direct and indirect influence of internal entrepreneurial factors. Research data were obtained through the distribution of questionnaires conducted online. Then collected and processed using the SmartPLS 4.0 application. The research process began with a pre-test of 30 respondents, then continued with actual data collection from 275 respondents. Based on the test results, it can be concluded that there is a significant positive relationship between entrepreneurial self-efficacy, entrepreneurial motivation, and entrepreneurial leadership with business performance. Conversely, no significant relationship was found between entrepreneurial innovative behavior and business performance.